Application of Core-Shell Modeled Composite Catalysts for Biofuel Production from Nonedible Vegetable Oils - Ramya, G.; Vaithiyanathan, R.; Amala Infant Joice, J.; Sudhakar, R.; Sivakumar, T. (Asian Journal of Chemistry, 2012)
In the present study we report the synthesis, characterization and catalytic activities of microporous HZSM-5, mesoporous AlMCM-41 and composite AlMCM-41/ZSM-5 catalysts. All the catalysts were synthesized by hydrothermal method. The formation of composite catalyst was confirmed by XRD, N2 sorption studies and SEM techniques. The catalytic activities were studied towards the cracking of jatropha and castor oils and the results are discussed.